RESPONSE OF DIFFERENT GREENGRAM (Vigna radiata L. Wilczek) CULTIVARS TO VARYING PLANT POPULATIONS - BRIJAL R. PATEL; D. K. PATEL; T. V. REDDY; GRISHMA N. PATEL; M. M. CHAUDHARY (The Bioscan, 2020)
Results revealed that greater plant height was obtained from plant density of 3.33 lakh plants/ha where as lower plant density of 2.22 lakh plants/ha produced significantly higher growth and yield attributes viz., number of branches/plant, pod length, number of seeds/pod and number of pods/plant over higher plant density. Plant density of 3.33 lakh plants/ha gave 25.93, 17.36 and 20.11 per cent higher seed, stover as well as protein yield, respectively over plant density of 2.22 lakh plants/ha. Significantly higher nitrogen, phosphorus and potassium uptake by plant was noted with plant density of 3.33 lakh plants/ha. Greengram variety GM 4 registered significantly taller plants at harvest, as also greater pod length and number of seeds/pod. The variety GM 4 took significantly lower number of days to 50 per cent flowering and physiological maturity and produced highest number of pods/plant, seed index, seed, stover and protein yield. GM 4 performed better by recording 12.93, 9.70 and 9.96 percent higher seed, stover and protein yield, respectively over variety Meha. Variety GM 4 significantly higher nitrogen, phosphorus and potassium uptake by plant was observed..